Complications of Ponseti Technique in Treatment of Idiopathic Club Foot - Redah, Samer Mohammed (AL-Kindy College Medical Journal, 2022)
Background: Clubfoot, or talipes equinovarus, is a congenital deformity that consist of; supination and adduction of the forefoot and midfoot; equinus of hindfoot and varus. It was found that more than 100,000 babies are born each year with congenital clubfoot Objectives: The purpose of this study was to investigate the complications of ponseti method for treatment of children with idiopathic club foot. Subjects and Methods: 50 children with 74 clubfeet were managed by Ponseti method from May 2019 to July 2020 in Al-Wasity teaching hospital with primary correction of the deformity followed sometimes by elongation of Achilles tendon then the patients were followed up till June 2021 and the complications were calculated. Results: complications were 10.8% incomplete correction (mostly equinus) and it was corrected by surgery, 6.7% ulcer on the medial surface of head of 1st metatarsal , 9.4% cast falling and 18.9% relapse. Conclusions: Ponseti technique is a safe and effective method for correction of clubfoot and decreases the need for corrective surgery with minimal complications that can be easily managed.